FE modelling strategies of weld repair in pre-stressed thin components - Salerno, Gervasio; Bennett, Chris; Sun, Wei; Becker, Adib A. (SAGE, 2016)
Two computational procedures have been developed in the commercial finite element (FE) software codes Sysweld and Abaqus to analyse and predict the residual stress state after the repair of small weld defects in thin structural components. The numerical models allow the effects of the repair to be studied when a pre-existing residual stress field is present in the fabricated part and cannot be relieved by a thermal treatment. In this work the modelling strategies are presented and tested by simulating a repair of longitudinal welds in thin sheets of Inconel 718 (IN718). Although the numerical strategies in the two codes are intrinsically different, the results show a significant agreement, predicting a notable effect imposed by the initial residual stress.